“I wish it had a place to go”: a nominal group study of barriers to the effectiveness of non-surgical treatments for knee osteoarthritis inclusive of minority populations - Jasvinder A. Singh (BMC, 2021)
Abstract Objective To examine patient experience, views, and opinions regarding the ineffectiveness of the current knee osteoarthritis (OA) treatments. Methods Nominal groups were conducted with consecutive clinic patients with knee OA, oversampling African Americans. Patients discussed and rank-ordered their concerns. Results Fourteen nominal groups with 48 knee OA patients were conducted with a mean age of 60.6 years (standard deviation, 9.8) and a knee OA duration of 7.8 years (sd, 5.4); 25% were men, and 54% were African American. The most frequently cited highly ranked concerns for the ineffectiveness of current knee OA treatments were as follows: (1) medication-related—(A) side effects (3 groups; 4% vote), (B) limited efficacy (5 groups; 11% vote), (C) medication not targeting underlying disease (7 groups; 16% vote), (D) lack of personalized medication use (3 groups; 4% vote), (E) temporary benefit (3 groups; 6% vote), and (F) fear of addiction/natural treatment preference (2 groups; 3% vote); (2) exercise/physical therapy-related—(G) exacerbation of joint pain (1 group; 3% vote), (H) difficulty in doing exercises (2 groups; 2% vote), (I) lack of motivation (8 groups; 12% vote), (J) technical challenges/lack of personalized exercise regimens (1 group; 1% vote), and (K) cost (2 groups; 3% vote); and (3) weight loss-related—(L) difficulty in achieving weight loss (4 groups; 6% vote) and (M) motivation (1 group; 1% vote). Conclusions A representative sample of participants with knee OA identified several barriers to the effectiveness of current knee OA treatments. This new knowledge provides insights for making the current treatment options potentially more usable and/or more effective.